Investigation of Al-ZERODUR interface by Raman and secondary ion mass spectroscopy - Berezhinsky, L.I.; Yukhymchuk, V.A.; Maslov, V.P.; Tetyorkin, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
The interface of ZERODUR ceramics and thin aluminium film was investigated by Raman and secondary ion mass-spectroscopy techniques. Possible chemical reactions at the interface is briefly analyzed and compared with experimental data. Contributions of amorphous and crystalline phases of ZERODUR to Raman spectra are discussed. Keywords: ZERODUR ceramics, Raman spectra, secondary ion mass-spectroscopy. Manuscript received 19.04.05; accepted for publication 18.05.05.